The design and synthesis of new transition metal coordination complexes as potential anti-malarial agents - Hager, Emma (Department of Chemistry, 2014)
New Rh(I), Rh(III), Ir(III) and Pd(II) coordination complexes bearing 1,10-phenanthroline (phen) or 2,2'-bipyridyl (bipy) ligands have been investigated for potential anti-malarial activity.